Pemaparan Kepelbagaian Budaya dan Agama dalam Filem Muallaf Arahan Yasmin Ahmad: The Representation of Multiculturalism and Religion in Yasmin Ahmad’s Muallaf - Ngo Sheau Shi; Harith Baharudin (Wacana Seni Journal of Arts Discourse, 2015)
Owing to its controversial portrayal of religious matters, Yasmin Ahmad's Muallaf (2008) had invited polemic against its release in the Malaysian cinema by the Film Censorship Board. Most criticisms of this film neglected the fact that film form is the central part of the signifying system that constructs what is commonly known as the dominant ideology of societies. This article shows how film text is used as a cultural artefact to produce what is described as spectatorship in film studies as a potentially ideologically embedded position to subjectivities within certain societal contexts. In this respect, this article is an effort to provide a detailed textual analysis of the film form on the portrayal of religious issues in terms of visual organisation and narrative structure through the framework of multiculturalism in order to evaluate the controversial criticism arising from arbitrary reading of the film by some film critics in Malaysia. Through the textual analysis, this article argues that the distinguished cinematic styles and forms employed in this film have constructed an alternative discourse, which drives one to question the dominant understanding of Islamic ideas that is promoted by conservative scholars, especially in the context of contemporary Malaysian society.